Understanding the Luminescence Characteristics of Ultraviolet InGaN/AlGaN Multiple Quantum Wells with Different In Gradients - Jie Zhang (MDPI AG, 2021)
The electroluminescence (EL) properties of InGaN/AlGaN ultraviolet light-emitting multiple quantum wells (MQWs) with identical average In content but different In gradients (In content increases linearly, along the growth direction) are investigated numerically. It is found that the luminescence efficiency is improved, and the EL spectral peak wavelength becomes longer for the MQW sample with a larger In gradient. Since the influence of In gradient is different for the conduction and valence bands in InGaN layers, the distribution of electrons and holes in QWs may be changed, leading to a redshift of EL spectra. In particular, when the In gradient increases, the overlap integral of electron-hole wavefunction in InGaN QWs increases, resulting in a higher radiative recombination rate and an enhanced EL intensity.